Simulation of Swirling Wet Steam Flow through a Supersonic Nozzle - A/L Vijayakumaran, Harrivin (IRC, 2016)
The subject matter of this paper is the swirling flow of wet steam through a supersonic nozzle. Various 2D nozzle designs were studied to find the best model to be used in this study. Multiple simulations were created using computational fluid dynamics and parameters were assigned to manage constraints and variables. A benchmarking process was then carried out to ascertain the accuracy of the designs. The results were analyzed and measured against pre-defined results to determine its legitimacy. The chosen convergent – divergent nozzle with verified geometry was subsequently modeled in 3D. Wet steam is simulated to flow normally through the convergent – divergent nozzle. Swirl is then introduced to the flow of wet steam by means of an angled inlet. Various wet steam flow parameters were measured at the entrance and exit of the nozzle